2018
DOI: 10.3390/coatings9010008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Pre-treatments to Improve the Weather Resistance of Polyurethane Coatings on Black Spruce Wood

Abstract: We hypothesize that plasma treatments that increase the adhesion and penetration of transparent water, and solvent-borne polyurethane coatings into black spruce wood will improve the performance of coated wood exposed to accelerated weathering. We tested this hypothesis by modifying wood samples with plasma for 30, 180, 600, and 1200 s, and measuring coating penetration and adhesion using light microscopy and a mechanical pull-off test, respectively. Plasma treatment did not improve coating adhesion, but the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…The oil did not completely cover the surface of the wood, but occluded some tracheids (arrowed in Figure 2c), while others were free of oil ( Figure 2c). Plasma treatment of unmodified wood removed (etched) the raised border and the internal membrane (margo and torus) of bordered pits creating large circular voids at the surface of the wood (arrowed in Figure 2d), as we have observed previously with other wood species [27,28].…”
Section: Appearance and Microstructure Of Hot-oil And Plasma Treated mentioning
confidence: 52%
See 3 more Smart Citations
“…The oil did not completely cover the surface of the wood, but occluded some tracheids (arrowed in Figure 2c), while others were free of oil ( Figure 2c). Plasma treatment of unmodified wood removed (etched) the raised border and the internal membrane (margo and torus) of bordered pits creating large circular voids at the surface of the wood (arrowed in Figure 2d), as we have observed previously with other wood species [27,28].…”
Section: Appearance and Microstructure Of Hot-oil And Plasma Treated mentioning
confidence: 52%
“…They contain a cellulosic membrane (the margo) and a centrally thickened torus. Pit membranes in untreated wood are rapidly etched by plasma [27,28], and they are also highly susceptible to microbial degradation [44]. However, remnants of pit membranes were commonly observed at the surface of hot-oil modified and plasma treated wood, whereas they were absent from the surface of unmodified plasma treated controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xia et al [19] prepared a polyurethane coating by applying ultraviolet light curing, added fluoro-acrylic monomer and mercaptan, and achieved a luster of 86.9 ± 0.9, which improved the hydrophobicity, mechanical properties, and yellowing properties of the coating. Haase et al [20] found that the water-based coating turned yellow at 3024 h with fewer defects after plasma modified coating, while the solvent-based coating began to show defects at 1008 h after accelerated weathering.However, water as a solvent shows several disadvantages, including poor dispersion ability, high surface tension, foaming, poor light and color retention, poor weather resistance, unstable performance of large areas of coating, easy to flow hanging, and other defects [21]. In order to obtain a reliable and stable coating, we refer to the tests performed by relevant experts and compare the tests with different formulas, focusing on the comparison of QUV aging reliability properties.…”
mentioning
confidence: 99%